Do Motor Imagery Performances Depend on the Side of the Lesion at the Acute Stage of Stroke? - Kemlin, Claire; Moulton, Eric; Samson, Yves; Rosso, Charlotte (Frontiers in Human Neuroscience, 2016)
Abstract Objective: To compare explicit and implicit motor imagery abilities in acute stroke patients (<3 weeks) and healthy subjects, and investigate the role of right or left hemisphere lesions on performance. Design: Observational study evaluating motor imagery performances Setting: Stroke-unit in Paris, France Subjects: Twenty-four stroke patients at the acute stage and 24 age- and gender-matched healthy volunteers Main measures: Subjects performed implicit (Hand Laterality Judgment Task) and explicit (number of imagined/executed hand movements) motor imagery tasks and a clinical motor assessment. Differences between healthy subjects and patients as well as the impact of lesion side on motor imagery were studied using ANOVA. We analyzed the relationship between motor executed and imagined movements (temporal congruence) using Pearson’s correlations. Results: For implicit imagery, stroke patients had slower reaction times (RTs, p=0.02) and higher error rates for the affected hand (p<0.01) yet shared similar characteristics (angle effect: p≤0.0001) with respect to healthy subjects. For the unaffected hand, right-sided stroke patients had a higher error rate and similar RTs whereas left sided stroke had higher RTs but similar error rate than healthy subjects. For explicit imagery, patients exhibited bilateral deficits compared to healthy subjects in the executed and imagined condition (p<0.0001 ). Patients and healthy subjects exhibited a temporal congruence between executed and imagined movements (p≤0.04) except for right-sided strokes who had no correlation for both hands. Conclusions: When using motor imagery as a tool for upper limb rehabilitation early after stroke, caution must be taken related to the side of the lesion